Helicobacter pylori: Interrelationship between the urea test in dental plaque samples and gastric biopsy - De la Cruz Valle, Daniel (2010)
With the purpose of establishing interrelationship between the urea test in dental plaque and gastric biopsy samples to determine the presence of Helicobacter pylori, this study was performed in 50 patients from the National Police Central Hospital. Simultaneously, samples from the dental plaque and gastric biopsies were taken from patients of the Gastroenterology Department, the same that were submitted to endoscopies by their medical attendant. Samples of their stomachs were obtained by a punching method, which were placed in urea broth and transported to the laboratory of the hospital for their incubation. The dental plaque samples were placed directly in the urea broth and taken to the Microbiology laboratory of the School of Dentistry of the San Marcos Major National University for their incubation at 37 ºC. The results were obtained 12, 48 and 72 hours later, and recorded into a database. The results from the gastric biopsies were obtained from the Histopathology laboratory of the Hospital. The analysis of the results obtained corroborates the hypothesis about the existence of a relationship between the determination of the positive urea test in dental plaque samples and the ones obtained from the gastric biopsies, since a 68 % coincidence of values was obtained, both positive and negatives. The specificity of the cases was of 62 % and the sensibility of 75 %. However, the interrelationship level is not high.